Combining ability and heterosis studies for oil and seed meal quality traits in Indian mustard (Brassica juncea L.) - Priyamedha; Arun Kumar; CS Mahto; ZA Haider (Journal of Oilseed Brassica, 2026)
The study of combining ability, and heterosis for oil and seed meal quality traits in 40 F1s of Indian mustard,developed from 8 lines, and 5 testers was carried out in randomized block design with two replications atCrop Research Centre of Birsa Agricultural University, Ranchi, India during Rabi 2014-15. Analysis ofvariance revealed, significant differences among genotypes for all the traits. Higher gca variance indicatedthe role of additive gene action in inheritance of these traits except saturated fatty acid, and linolenic acid.The parents, Shivani and Heera were good combiner for most of the quality traits. Estimation of specificcombining ability effects of crosses viz., NRCHB 101 x Heera, Pusa Bold x Pusa Mustard-21, Shivani xHeera, Pusa Mustard-25 x RGN-73, and BAUSM 92-1-1 x Pusa Mustard-21 were highly significant forglucosinolate content, erucic acid, oleic acid, and linoleic acid. Considering mean performance, and generalcombining ability effect, the parent, Heera was found promising for glucosinolate content, linoleic acid, anderucic acid. On the basis of mean performance, specific combining ability effect, and heterobeltiosis, thecrosses, BAUSM 92-1-1x Pusa Mustard-21 for linoleic acid, and erucic acid, Shivani x BPR 543-2 forsaturated fatty acid, NRCDR-02 x RGN-73 for linolenic acid, and NRCDR-02 x Heera for glucosinolatecontent were found promising. The cross, Shivani x Heera was found to be most promising showing desirabilityfor maximum number of quality traits. Selection in early segregating generation is suggested to be moreeffective for breeding for quality traits in Indian mustard as most of them were found to be controlled byadditive genes action.